Paris-Tel Aviv: Forgetting as Memory - Ora Avni (Studies in 20th & 21st Century Literature, 1999)
The definition of collective identity has been at the heart of our fin de siècle's preoccupations...
Keywords: collective identity; fin de siècle; preoccupation; Paris-Tel Aviv